Iron‐Catalyzed Decarboxylation of Trifluoroacetate and Its Application to the Synthesis of Trifluoromethyl Thioethers. Issue 48 (20th October 2015) - Exner, Benjamin; Bayarmagnai, Bilguun; Jia, Fan; Goossen, Lukas J.
Abstract: Nucleophilic CF3 has been generated by decarboxylation of potassium trifluoroacetate, arguably the most easy‐to‐handle, inexpensive, and sustainable source of trifluoromethyl groups. Simple iron(II) chloride catalyzes the decarboxylation as well as a subsequent trifluoromethylation of organothiocyanates, resulting in a straightforward synthesis of trifluoromethyl thioethers. The KCN byproduct is absorbed by iron(II) with formation of nontoxic potassium hexacyanoferrate. An analogous trifluoromethylation of aldehydes with trifluoroacetate underlines the synthetic potential of such iron‐catalyzed decarboxylative trifluoromethylations. Abstract : Simple iron(II) chloride catalyzes the decarboxylation of potassium trifluoroacetate, arguably the most easy‐to‐handle, inexpensive, and sustainable source of trifluoromethyl groups. This opens up opportunities for straightforward nucleophilic trifluoromethylations, including the synthesis of trifluoromethyl thioethers from easily available organothiocyanates depicted above.